4+3(h+1)=4h+6

Simple and best practice solution for 4+3(h+1)=4h+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+3(h+1)=4h+6 equation:


Simplifying
4 + 3(h + 1) = 4h + 6

Reorder the terms:
4 + 3(1 + h) = 4h + 6
4 + (1 * 3 + h * 3) = 4h + 6
4 + (3 + 3h) = 4h + 6

Combine like terms: 4 + 3 = 7
7 + 3h = 4h + 6

Reorder the terms:
7 + 3h = 6 + 4h

Solving
7 + 3h = 6 + 4h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-4h' to each side of the equation.
7 + 3h + -4h = 6 + 4h + -4h

Combine like terms: 3h + -4h = -1h
7 + -1h = 6 + 4h + -4h

Combine like terms: 4h + -4h = 0
7 + -1h = 6 + 0
7 + -1h = 6

Add '-7' to each side of the equation.
7 + -7 + -1h = 6 + -7

Combine like terms: 7 + -7 = 0
0 + -1h = 6 + -7
-1h = 6 + -7

Combine like terms: 6 + -7 = -1
-1h = -1

Divide each side by '-1'.
h = 1

Simplifying
h = 1

See similar equations:

| 2.50=1201.10 | | 9-2k=11 | | -1/50+-2=4 | | 10[y+5]=10 | | 500=45x+35(12-x) | | 11-8x-4x^2=0 | | 9y=9y-15 | | 9x-2+5(x+9)=85 | | 77x+25x=400+25x | | -15x+11=86 | | 3x+6(x+5)=-51 | | 2x+200=800-22x | | 166=s+s+2+26+s | | 166=s+s+2+26s | | 10c-9=8c+5 | | 10-2(x+3)=4 | | -14+3n+30=14n+28+n | | 11m+2n+4m-n= | | (4/9)(5/18) | | 14a-4a+5a-3a= | | 5+18/2*4 | | -2+x/-2=-12 | | 3w+7=-5 | | 2(3r-4)-6(t+1)=-t+4(t+10) | | 3+22+5x=10x | | 4/9x5/18 | | -6=x/-13-2 | | 3y+4=4 | | X/2+5=25 | | 7(y+4)=2x+5 | | x^5+1x^3-12x=0 | | -61=-3x-10 |

Equations solver categories